FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MELAKUKAN PEMBELIAN PRODUK PADA PT LONG TIME BATAM - Hendri Herman (LPPM Universitas Putera Batam, 2019)
This study aims to look at the factors that influence consumer decisions in making purchases. The object of research is PT Long Time Batam, with a population of 135 people. calculation of the number of samples using the Slovin formula, so that the number of samples obtained is 100 respondents. from the results of the study note that the promotion has a significant influence on purchasing decisions. The effect of promotion on consumer decisions in making purchases is 42.2%